2021
DOI: 10.2196/28079
|View full text |Cite
|
Sign up to set email alerts
|

Serious Games Are Not Serious Enough for Myoelectric Prosthetics

Abstract: Serious games show a lot of potential for use in movement rehabilitation (eg, after a stroke, injury to the spinal cord, or limb loss). However, the nature of this research leads to diversity both in the background of the researchers and in the approaches of their investigation. Our close examination and categorization of virtual training software for upper limb prosthetic rehabilitation found that researchers typically followed one of two broad approaches: (1) focusing on the game design aspects to increase e… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 71 publications
0
17
0
Order By: Relevance
“…The virtual Box and Block Test was the only functional assessment of the upper extremity in those studies. Therefore, with current empirical evidence, a knowledge gap still exists to which extent virtual reality–based upper extremity prosthetic training leads to skill transfer to motor performance and participation in real-world daily activities 38 . More clinical trials with rigorous quality are suggested to answer this question by adopting domains of the International Classification of Functioning, Disability and Health framework 39 and using valid outcome measures.…”
Section: Discussionmentioning
confidence: 99%
“…The virtual Box and Block Test was the only functional assessment of the upper extremity in those studies. Therefore, with current empirical evidence, a knowledge gap still exists to which extent virtual reality–based upper extremity prosthetic training leads to skill transfer to motor performance and participation in real-world daily activities 38 . More clinical trials with rigorous quality are suggested to answer this question by adopting domains of the International Classification of Functioning, Disability and Health framework 39 and using valid outcome measures.…”
Section: Discussionmentioning
confidence: 99%
“…This can possibly happen with a successful generalization if the training is adequately designed with solutions like task switching (Heerschop et al 2021). Overall, the training designers should focus not only on playfully engaging the user to train the muscles, but also on accurately representing prosthetic use tasks to enable the related skills transfer (Garske et al 2021a). Furthermore, the parameters of meaningful and, possibly, ecological interactive settings can be experimentally controlled by the clinician or the researcher (Resnik et al 2011, Bouwsema et al 2014, Markovic et al 2017, Paljic 2017, Nissler et al 2019, Boschmann et al 2021, Phelan et al 2021.…”
Section: Toward User-centered Upper Limb Prostheticsmentioning
confidence: 99%
“…Therefore the assumption is that when one improves their myocontrol in the game, the learned skill will transfer to actual prosthesis use and as a consequence users will improve their ability to control the prosthesis. Even though several studies have been performed on serious game training for upper limb prosthesis in the past decade ( 11 , 12 , 16 , 17 , 19 , 20 , 29 , 34 , 37 39 ), the most effective game design to facilitate transfer from the game to actual prosthesis use has not been established. One reason for this might be that people differ in the way their individual motor learning processes are stimulated best as well as in their overall motor learning capacities ( 40 45 ).…”
Section: Introductionmentioning
confidence: 99%
“…A task-specific serious game for prosthesis control should resemble tasks that a prosthesis user might encounter in their day-to-day life, such as opening and closing of a prosthesis hand (i.e., proportional control) or switching between different grips (i.e., switch control) ( 10 , 17 , 21 ). Transfer effects were found previously after training with a task-specific serious game, but not after training with a non-task-specific serious game ( 9 ).…”
Section: Introductionmentioning
confidence: 99%